Prevention of pornography in vocational school students - Cinthya Indah Permata Sari; Firman Firman (International Journal of Applied Counseling and Social Sciences, 2021)
The high number of pornography among teenagers is a real problem for teenagers, especially when the right solution has not been found in preventing student pornography. Even though it is known that pornography cases are increasing every year. The purpose of this study was to measure the meaning of adolescent life and the prevention of pornography for SMK students in Padang City. This research is a descriptive research with quantitative approach using pornography prevention instruments with validity greater than 0.325 and reliability 0.895. The subjects of this study were vocational high school students in the city of Padang. Subjects were taken with simple random sampling technique. The study used data analysis techniques and descriptive analysis. The results showed that there were several levels of pornography in students, and students' lives were affected by pornography such as high level student pornography at 12%, moderate pornography at 82.63% and low at 5.3%. The results of this study can be used as information for teachers. guidance and counseling to prevent student pornography in the lives of vocational youth in the city of Padang.